Implementasi Pembelajaran Akidah Akhlak Terhadap Perilaku Siswa Di MTS Al-Azhar Menganti Gresik - Wanda Dewi Artika; Achmad Khusnan; Barudin Barudin (Jurnal Inovasi Pembelajaran dan Pendidikan, 2025)
This research was motivated by the fact that negative student behaviors were still found at MTs Al-Azhar Menganti, such as lack of discipline, mocking peers, and reluctance to help others, despite receiving Aqidah Akhlak instruction. This indicates a gap between the objectives of learning and its implementation in practice. The purpose of this study was to examine the implementation of Aqidah Akhlak learning, describe students’ behavior, and analyze its influence on their character development. This study employed a qualitative case study approach with data sources consisting of Aqidah Akhlak teachers, eighth-grade students, and supporting documents. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The findings reveal that Aqidah Akhlak learning was implemented based on the Ministry of Religious Affairs’ curriculum and adapted to the pesantren culture, emphasizing role modeling and religious habituation. The implementation positively affected students’ behavior, particularly in discipline, politeness, and participation in religious activities. However, challenges remain, including negative behavior among some students and limited teaching media. Therefore, the success of Aqidah Akhlak learning requires continuity, innovative teaching methods, and collaboration between teachers, parents, and the community.